ANALYSYS OF CONSUMER SATISFACTION OF DBD POWDER BEVERAGE PRODUCTS, MEDAN BRANCH INCREASING SALES - Nurhayati HasanahNurhayati Hasanah; Cece Cece (Jurnal Ekonomi, 2023)
The data analysis technique used in this study is data analysis technique in quantitative research using statistics. So this study uses statistical inference. Which statistical inference is a part of statistics that studies the interpretation and drawing conclusions that apply in general from the available data, namely the Analysis of Consumer Satisfaction in Increasing Sales of the Medan Branch of DHF Powder Case Study. This study shows that there is a positive influence between customer satisfaction and increased sales. The purpose of this study was to determine the effect of customer satisfaction on increased sales. It can be concluded that there is a positive influence simultaneously on customer satisfaction on increasing sales, meaning that the higher the customer satisfaction, the higher the number of sales, and vice versa. The purpose of this study was to determine the effect of customer satisfaction on increased sales. It can be concluded that there is a positive influence simultaneously on customer satisfaction on increasing sales, meaning that the higher the customer satisfaction, the higher the number of sales, and vice versa.